The Effect of Hypnobirthing Relaxation on the Anxiety Level of Third Trimester Primigravida Mothers in Facing Childbirth Preparations in the Working Area of the Naras Health Center, Pariaman, Indonesia - Silvia, Elwitri; Zaini, Hanifa; Marissa, Novi (Archives of The Medicine and Case Reports, 2024)
Pregnancy is a normal physiological process, but it can cause anxiety in pregnant women, especially in the third trimester. Anxiety in pregnant women can be caused by various factors, such as physical and hormonal changes, as well as fear of childbirth. Hypnobirthing relaxation is one method that can be used to reduce anxiety in pregnant women. This study aims to determine the effect of hypnobirthing relaxation on the anxiety level of third trimester primigravida mothers in preparing for childbirth in the working area of the Naras Health Center, Pariaman, Indonesia. This research uses a quasi-experimental research design with a pre-test and post-test approach. The research sample was 30 third trimester primigravida mothers in the working area of the Naras Health Center, Pariaman, Indonesia, who were divided into two groups, namely the intervention group that was given hypnobirthing relaxation and the control group that was not given hypnobirthing relaxation. The results showed that there was a significant difference between the anxiety levels of third trimester primigravida mothers in the intervention group and the control group after being given hypnobirthing relaxation (p<0.05). This shows that hypnobirthing relaxation can reduce the anxiety level of third trimester primigravida mothers in preparing for childbirth.